Structure and optical properties of [Ba1-xY2x/3](Zr0.25Ti0.75)O-3 powders - Sczancoski, J. C.; Cavalcante, L. S. [UNESP]; Badapanda, T.; Rout, S. K.; Panigrahi, S.; Mastelaro, V. R.; Varela, José Arana [UNESP]; Li, M. Siu; Longo, Elson [UNESP] (Elsevier B.V., 2010)
[Ba1-xY2x/3](Zr0.25Ti0.75)O-3 powders with different yttrium concentrations (x = 0, 0.025 and 0.05) were prepared by solid state reaction. These powders were analyzed by X-ray diffraction (XRD). Fourier transform Raman scattering (FT-RS), Fourier transform infrared (FT-IR) and X-ray absorption near-edge (XANES) spectroscopies. The optical properties were investigated by means of ultraviolet-visible (UV-vis) absorption spectroscopy and photoluminescence (PL) measurements. Even with the addition of yttrium, the XRD patterns revealed that all powders crystallize in a perovskite-type cubic structure. FT-RS and FT-IR spectra indicated that the presence of [YO6] clusters is able to change the interaction forces between the O-Ti-O and O-Zr-O bonds. XANES spectra were used to obtain information on the off-center Ti displacements or distortion effects on the [TiO6] clusters. The different optical band gap values estimated from UV-vis spectra suggested the existence of intermediary energy levels (shallow or deep holes) within the band gap. The PL measurements carried out with a 350 nm wavelength at room temperature showed that all powders present typical broad band emissions in the blue region. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Ba(Zr,Ti)O-3; Vacancies; Lattice defects; Band gap; Photoluminescence